An Experientially Derived Model of Flexible and Intentional Actions for Weight Loss Maintenance After Severe Obesity - Natvik, Eli; Råheim, Målfrid; Andersen, John Roger; Moltu, Christian (Frontiers in Psychology, 2019)
Background Knowledge about non-surgical weight loss (WL) is scarce among people with severe obesity (SO). Lifestyle changes are primarily self-driven, occasionally accompanied by professional guidance and weight-management support. Weight regain and intervention discontinuation are common challenges among guidance and support programmes. In the current study, we describe a model of meaningful strategies for maintaining WL after SO based on the experiences of successful cases. Methods Aiming to investigate the experiences of WL and weight loss maintenance (WLM) (≥5 years) following SO, we designed a qualitative study. Ten adults of Norwegian ethnicity, eight women and two men aged from 27 to 59, participated in individual in-depth interviews. We recruited participants living in rural districts and cities across all four regions of Norway. The interviews concentrated on participants’ experiences of losing weight and maintaining a lower weight over the long term. The transcripts were analysed with a rigorous method for thematic cross-case analysis, namely, systematic text condensation (STC). Results Participants identified four experiential themes at the core of long-term WLM: (a) Owning the decision, (b) Creating self-reinforcement, (c) Sustaining a lifestyle-forming identity, and (d) Selecting support appropriate to one’s own situation. These core themes represent the intentional level, functioning both as the foundation of and the momentum for sustaining WL. On the behavioural level, participants continued to take action for change, obtain results, record and reflect on their efforts and milestones, observe what worked and felt good, and receive recognition from others, thereby realising changes. Conclusion Based on these results, we propose a model of WLM after SO, suggesting that practices toward WLM on the behavioural level achieve meaning and sustainability through their relationship with a core intentional level found across participants’ experiences. One implication is that the relationship between the intentional and behavioural levels might be more meaningful when discussing long-term WLM than the behaviours themselves.